MANAGEMENT ACCOUNTING PRACTICES, FOR DECISION MAKING (Costos y Gestión, 2020)
Management accounting is gaining strength in companies, because of the amount of competitiveness, changes in the corporate environment, markets internationalization and globalization, due to the speed of the updates in the information systems. The aim of this study is to evaluate the use of management accounting tools that are used by industrial companies in the city of Ambato-Ecuador. This a descriptive-explanatory study, where the management accounting development in industrial companies is described, the cost historic alternative criteria are characterized when developing their internal information, determining the price variations that can happen in the company. Also, some surveys with open questions are conducted for managers and accountants in order to obtain more information regarding fifty-two companies a subscribed capital of $100.00 (one hundred dollars). It is important to remark that these companies were selected because of their patrimonial structure. These companies should use a management accounting tools. As a final result, management tools used by these industrial companies are identified. This is how according to the management accounting concept such as the companies’ needs, the surveyed people replied that the preparation of the accounting information is carried out based on the use of a management accounting tools, given that it makes it possible a correct planning, control and evaluation of the resources. However, not all companies used a management accounting tools, whether because of a lack specialization or a lack resources for its application.
Keywords: management accounting; tools; decision making; activity based costing; variable costing and full costing